An Analysis of Slang Word in Avril Lavigne Song Lyrics “Head Above Water” - Siti Aisyah; Afriliana Larasati (JELT: Journal of English Language Teaching, 2021)
This study deals in the slang word analysis in Avril Lavigne song lyrics “Head Above Water” album. This study aimed to identify the types of slang word found in Avril Lavigne song lyrics “Head Above Water” album, to find out the meaning of slang word in Avril Lavigne song lyrics “Head Above Water” album, to analyze the slang word which are realized in Avril Lavigne song lyrics “Head Above Water” album. Descriptive qualitative research was applied in this study. The data of research were taken from Avril Lavigne song lyric “Head Above Water” album, 74 words found in this song. The data were analyzed by identifying the song into four types of process, classifying the word in each type of slang, analyze the data into the slang word. It was found that there were four types of slang in selected Avril Lavigne song lyrics “Head Above Water” album namely blending, coinage, clipping, and compounding. The writer found the most widely types of slang namely clipping among words of slang in selected 8 songs lyrics of Avril Lavigne “Head Above Water” album. The researcher was realized that the words where the slang word which was found in Avril Lavigne song lyrics “Head Above Water” album by reading all the lyrics in detail and analyzing the word by trying find the correct word or the real meaning, then the researcher can decide the word was called the slang word.Key words: Analysis, Slang Word, Avril Lavigne Song Lyrics